An Experimental Investigation of the Patterns of International Trade - Noussair, Charles N.; Plott, Charles R.; Riezman, Raymond G. (American Economic Review, 1995)
This paper studies a laboratory economy with some of the prominent features of an international economic system. The patterns of trade and output predicted by the law of comparative advantage are observed evolving within the experimental markets. Market prices and quantities move in the direction of the competitive equilibrium, but the quantitative predictions of the (risk-neutral) competitive equilibrium are rejected. Considerable amounts of economic activity occur as disequilibria. Factor-price equalization is observed, but there is a universal tendency for factors of production to trade at prices below their marginal products.